(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The private sector is actually playing a crucial role in the Indian economy. The significance of this sector at the economy of the nation may be visualized from the reality that it contributes to the main part of national income and employment. As a result, even after creating an enormous volume of investments in the public sector and finishing much more than fifty years of preparation, the Indian economy remains broadly depending on the private sector. The paper appears at the contribution of the private initiatives to commit as well as try to get materials in a globalized world and also the difficulties that it faces in realizing the full potential of its. It notes the benefits of economic diplomacy in an interdependent environment as well as places India’s projects for exactly the same in perspective.